2021
DOI: 10.3390/ijms222111375
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of Monocyte Subsets and PD-L1 Expression but Not T Cell PD-1 Expression in Obstructive Sleep Apnea Patients upon PAP Therapy

Abstract: Obstructive sleep apnea (OSA) is characterized by nocturnal breathing intermissions resulting in oxidative stress and eventually, a low-grade systemic inflammation. The study aimed to investigate the impact of positive airway pressure (PAP) therapy on the inflammatory milieu as measured by monocyte and T cell phenotypic alterations. Participants were assessed for their OSA severity before PAP therapy and about six months later, including patient-reported outcome and therapy usage by telemetry readout. The dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…We have recently shown, that OSAS patients revealed a significant restoration of monocyte subsets and monocytic PD-L1 expression upon CPAP treatment [ 25 ]. The present study is the first to address OSAS-induced immunological changes in terms of the influence of HNS therapy on a cellular level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently shown, that OSAS patients revealed a significant restoration of monocyte subsets and monocytic PD-L1 expression upon CPAP treatment [ 25 ]. The present study is the first to address OSAS-induced immunological changes in terms of the influence of HNS therapy on a cellular level.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy individuals, they both account for about 5–10% of peripheral blood monocytes. Increased abundances of pro-inflammatory CD16 + subsets have been associated with different acute and chronic inflammatory diseases [ 25 , 26 ]. The three circulating monocyte subsets all have the ability to acquire macrophage morphology and characteristics, but the exact potential of each subset is still unclear [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite all limitations and difficulties involved in the analysis of immune cells and especially the interpretation of the data, the consideration of this complex topic may provide relevant links to other related topics, such as the oncologic outcome of patients with head and neck cancer ( 54 ), which could be further investigated with markers expressed on immune cells (e.g., PD-1/PD-L1; 21 , 43 , 55 ). Considering that OSA is an inflammatory trigger and risk factor for cardiovascular disease and other comorbidities, we see great perspective opportunities to use immunological activity parameters as a surrogate for the response of OSA patients to therapies or as a starting point for the development of new therapeutic concepts.…”
Section: Discussionmentioning
confidence: 99%
“…We have found only one study to date investigating the effects of PAP therapy on the human cellular immune system ( 43 ). Although this pilot study has reported very interesting results, it should be critically considered due to the relatively small patient cohort (25 patients) and the non-standard method of OSA-diagnosis in the respective cohort; some participants were tested by polygraphy while others by polysomnography, potentially confounding results.…”
Section: Cellular Immunity and Osamentioning
confidence: 99%